Totalitarianism versus Democracy in The Hunger Games Trilogy: Foucauldian Discourse and Power Relations - Fella Mutiara (English Department, Faculty of Humanities, Andalas University, 2015)
This article discusses two political systems in The Hunger Games trilogy written by Suzanne Collins. The trilogy consists of The Hunger Games (2008), Catching Fire (2009), and Mockingjay (2010). The works reflect at least two political systems which are totalitarianism and democracy, and the confrontation between Capitol that applies totalitarianism and the rebels who put hopes on democracy. After the rebels win the war against the totalitarian Capitol, they and all citizens soon expect democracy would bring better lives. In analysing whether democracy fails for them or not, the writer uses Foucauldian discourse and power relations which argue that discourses have strong relationship with power. People tend to believe democracy to be the most humane political arrangement, while totalitarianism is all about total control. Democracy especially refers to freedom. This concept of freedom has now changed both in matter of meaning and practice. Comparing the discourses on totalitarianism and democracy in the books, one can see democracy has become a troublesome system similar to totalitarianism. However, using Foucauldian discourse and power relations has brought the writer to the conclusion that democracy in this trilogy is totalitarianism in disguise.Keywords: political system, totalitarianism, democracy, freedom, total control, discourse, disguise.